Development of specific nanobodies (VHH) for CD19 immuno-targeting of human B-lymphocytes - Banihashemi, Seyed Reza; Hosseini, Ahmad Zavaran; Rahbarizadeh, Fatemeh; Ahmadvand, Davoud (Iranian journal of basic medical sciences, 2018)
CD19 is a transmembrane glycoprotein of immunoglobulin superfamily. In order to treat lymphoma, monoclonal antibodies (mAb) can target different antigens, including CD19, CD20 and CD22 on the surface of B-cells. Along with biotechnology progress, a new generation of antibodies is introduced, with the purpose of eliminating the defects of the previous generation. Among the most developed one are nanobodies (Nb). Nbs are a unique kind of camelid single domain antibody fragments with a broad range of medical applications. Unique physicochemical properties of Nbs have made them ideal candidates for therapeutic and diagnostic applications. An immune gene library was created, and several CD19 specific Nbs were selected through antigen panning process, and their molecular properties as well as specificity, sensitivity, affinity and immunoreactivity against CD19 positive and negative cells were evaluated. The Nb library was prepared with 7.2 x107 members. We managed to isolate a panel of CD19-specific Nbs after the last round of selection with the affinity of isolated Nbs being estimated at the standard range of 15-35 nM. Sequence analysis of positive clones was indicative of the fact that 12 variable sequences were confirmed. Of all these 12 clones, 2 clones with the greatest level signal in ELISA underwent subsequent analysis. Our sequencing results indicated high sequence homology (approximately 90%) between the Nb and Homa variable immunoglobulin domains. Specific Nbs possess the potential to be used as novel therapeutic approaches in order to treat autoimmune diseases and B-cell lymphoma.